Panglima Laot and Contributions in Upholding Customary Law in Aceh's Maritime Regions (Panglima Laot dan Kontribusinya dalam Penegakan Hukum Adat di Perairan Aceh) - Susetyo, Heru; Febriyanto, Satrio; Laidinar, Shaubi; Ilahidayah, Wahyumi; Febriansyah, Muhammad; Mahilaveda, Nadila (The Indonesian Journal of Socio-Legal Studies, 2023)
Panglima Laot has been felt in Aceh since the era of Sultan Iskandar Muda and is still known today. Panglima Laot is not part of the Aceh government but is recognized as Aceh's cultural heritage. Later, Panglima Laot was also regulated in the Aceh Qanun as the living law in Aceh. Culturally, it can be said that the Marine Commander is the leader of the fishermen in Aceh, whose job is to coordinate the fishermen, maintain maritime security according to their respective territories, and conserve Aceh's marine environment. This article examines the existence of Panglima Laot in Aceh in this contemporary era. With an emphasis on their role in upholding customary law in Aceh waters. The data was obtained through field research in Aceh and library data studies. The findings from this study are that Panglima Laot in Aceh still exists and plays a significant role in upholding customary law in Aceh waters. Coexist in harmony with national law and other legal systems that live in Aceh.